150 Ecg Problems - John R. Hampton (USA Churchill Livingstone, 2008)
This third edition includes 150 real clinical case histories and their accompanying ECG readouts. The reader is asked to report and interpret each ECG and draw up a plan for the patient's clinical management.
Includes index.
Keywords: Applied Sciences (3GdYdhe GdJWHjbjIs; General; Electrocardiography -- Problems, exercises, etc; Electrocardiography; Electrocardiography -- Problems and exercises